2021
DOI: 10.1021/acsnano.1c02636
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolding of Gold and Gold–Silicon Heterostructures at Room Temperature

Abstract: Nanofabrication techniques are limited by at least one of the required characteristics such as choice of material, control over geometry, fabrication requirements, yield, cost, and scalability. Our previously developed method of thermomechanical nanomolding fulfills these requirements, although it requires high processing temperatures. Here, we demonstrate low-temperature molding where we utilize the enhanced diffusivity on "eutectic interfaces". Gold nanorods are molded at room temperature using Au−Si alloy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Irradiation of the Au NP on the bare Si substrate only results in red shift of the scattering peak (Figure a) and the spherical Au deforms into a NP with a small plate underneath (inset of Figure a and Figure S4). This is largely because Au–Si alloys can be formed at the interface, which significantly lowers the melting point of Au and the interfacial tensions . Thus, partial wetting of the molten Au is formed on the Si substrate, which forms the small plate on Si.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Irradiation of the Au NP on the bare Si substrate only results in red shift of the scattering peak (Figure a) and the spherical Au deforms into a NP with a small plate underneath (inset of Figure a and Figure S4). This is largely because Au–Si alloys can be formed at the interface, which significantly lowers the melting point of Au and the interfacial tensions . Thus, partial wetting of the molten Au is formed on the Si substrate, which forms the small plate on Si.…”
Section: Resultsmentioning
confidence: 99%
“…This is largely because Au−Si alloys can be formed at the interface, which significantly lowers the melting point of Au and the interfacial tensions. 27 Thus, partial wetting of the molten Au is formed on the Si substrate, which forms the small plate on Si. The large surface tension of the molten Au droplet still retains its hemispherical shape, rendering the formation of NP on plate structure.…”
Section: Resultsmentioning
confidence: 99%
“…According to Liang et al [53], the optimal temperature for achieving nematic, curved end-to-end assembly and transition mode is 30 ° C-50 ° C on a wrinkled template. Moreover, GNRs can be molded at room temperature using Au-Si alloy as feedstock [54]. By thermal annealing the GNRs after the evaporation of the solvent and gradually increasing the temperature from 20°C to 140°C, a quasicontinuous wire-like structure was obtained [28].…”
Section: Self-assembly By Variation Of Temperature and Humiditymentioning
confidence: 99%
“…In low humidity, GNRs tend to form the nematic arrangement, while in high humidity, GNRs prefer the curved end-to-end fashion as mentioned in ref. [54].…”
Section: Self-assembly By Variation Of Temperature and Humiditymentioning
confidence: 99%
“…The nanowires’ length and diameter are limited practically by the mold dimensions, but there is no fundamental limit to these features. We have demonstrated that TMNM can be applied to a wide range of materials, including metals, alloys, and ordered phases. , The underlying mechanism of TMNM is based on diffusion, specifically on interface diffusion (see Figure S2 Supporting Information) for temperatures above ∼0.4 T M , where T M is the melting temperature of the material. Notably, functional nanostructures fabricated by TMNM include superconductors, topological insulators, semiconductors, and phase change materials .…”
mentioning
confidence: 99%